BATIK OEY SOE TJOEN KONSISTENSI TRADISI DAN KUALITAS BATIK ENCIM DI PEKALONGAN - Purnomo, Muh. Arif Jati (Institut Seni Indoensia Surakarta, 2009)
The research is conducted to answer various problems about how batik encim style in Pekalongan in generally is and especially batik â€œOey Soe Tjoenâ€. Beside it is also conducted to answer the question about what the tradition and quality that wanted to be maintained from batik â€œOey Soe Tjoenâ€ products. The purposes of the research are to describe and document batik encim style or batik style getting influence from China culture in Pekalongan, especially batik Oey Soe Tjoen. The research will use aesthetic approach by using E.B. Feldman theory to answer the various problems. The credibility of data is secured by the application of method and source of triangulation. The research concludes that batik Oey Soe Tjoen style, which is one sample of batik encim in Pekalongan has different characteristics with batik encim style occurred outside Pekalongan, especially on the process of flower, leaves, and soil form done in the detail and perfect quality of making. The consistency or the steadiness in keeping the quality of tradition that has been thought by their parents, related with technique, equipment, material, and pattern is still strongly maintained. Based on that condition , it is possible to become one of reasons why batik Oey Soe Tjoen can survive in facing market competition whichÂ